2020
DOI: 10.1037/ppm0000224
|View full text |Cite
|
Sign up to set email alerts
|

Online original TV series: Examining portrayals of violence in popular binge-watched programs and social reality perceptions.

Abstract: Cultivation theory asserts that heavy exposure to universal themes on TV lead viewers to see the world in ways that parallel TV. This research applies cultivation theory to a contemporary context by considering portrayals of violence in online original TV series. In Study 1, a content analysis of commonly binge-watched online original TV programs revealed 5.9 violent instances per hour, generally characterized as explicit, serious, significant, graphic, and intentional. Moral justification of violence was rare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
10
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 34 publications
3
10
0
2
Order By: Relevance
“…Violence is a common theme in video games (Hartmann et al, 2014) as well as in other forms of entertainment media, including TV programs (Hetsroni, 2007; Krongard & Tsay-Vogel, 2020), films (Bushman et al, 2013), music videos (Martin & Collins, 2002), and even advertisements (Jones et al, 2014). Indeed, violence is a common theme even in media rated as appropriate for children, such as in E-rated video games for “Everyone” (Thompson & Haninger, 2001) and in G-rated films for “General Audiences” (Yokota & Thompson, 2000).…”
mentioning
confidence: 99%
“…Violence is a common theme in video games (Hartmann et al, 2014) as well as in other forms of entertainment media, including TV programs (Hetsroni, 2007; Krongard & Tsay-Vogel, 2020), films (Bushman et al, 2013), music videos (Martin & Collins, 2002), and even advertisements (Jones et al, 2014). Indeed, violence is a common theme even in media rated as appropriate for children, such as in E-rated video games for “Everyone” (Thompson & Haninger, 2001) and in G-rated films for “General Audiences” (Yokota & Thompson, 2000).…”
mentioning
confidence: 99%
“…Their observations confirmed that watched content influences the perception of reality [6]. In 1969, George Gebner proposed a cultivation theory in which intense exposure to universal themes on television leads viewers to perceive the world as depicted on screen [7]. A decade later, the researcher and his team observed the so-called 'mean world syndrome', which is associated with higher levels of anxiety and a pessimistic perception of reality in people exposed to violent content [8] [9].…”
Section: Introductionmentioning
confidence: 85%
“…The first aspect determines the frequency, e.g., determining the number of crimes, and the second aspect determines the probability of given events, e.g., feeling how likely a person is to be a victim of violence [19,20]. In the 70's and 80's of the twentieth century, violence accounted for 80% of the time of television programmes during prime time, so it was thought that a viewer who watched television for a large proportion of the time might perceive the world as a more violent, ruthless and crimeridden place, and at the same time might show a higher level of aggression himself [7,19].…”
Section: Effects Of Viewed Content On Perceptions Of Reality: Cultiva...mentioning
confidence: 99%
See 1 more Smart Citation
“…While the prevalence in Italy is far lower—30% according to the EU-Project (2012)—there are worrying signals of a culture that seriously underrates many forms of sexual violence in society at large and in university settings. Newspaper reports, television programs, and posts on social networks show that sexual violence is often treated as a joke or attributed to provocations by the victim (Krongard, & Tsay-Vogel, 2018; Maass et al, 2003; Ward, 2016).…”
mentioning
confidence: 99%